2022
DOI: 10.3390/molecules27103202
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Spiramycin in LPS-Activated RAW 264.7 Macrophages

Abstract: Drug repurposing is a simple concept with a long history, and is a paradigm shift that can significantly reduce the costs and accelerate the process of bringing a new small-molecule drug into clinical practice. We attempted to uncover a new application of spiramycin, an old medication that was classically prescribed for toxoplasmosis and various other soft-tissue infections; specifically, we initiated a study on the anti-inflammatory capacity of spiramycin. For this purpose, we used murine macrophage RAW 264.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…It has been reported that, when the macrophage is stimulated with LPS, IκBα is phosphorylated and ubiquitinated. Accordingly, phosphorylated NF-κB is translocated from the cytoplasm to the nucleus to increase the inflammatory cytokine [ 9 , 10 , 11 ]. Western blot experiments were performed to investigate whether xanthotoxol inhibits the production of inflammatory cytokines through the NF-κB signaling pathway in LPS-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, when the macrophage is stimulated with LPS, IκBα is phosphorylated and ubiquitinated. Accordingly, phosphorylated NF-κB is translocated from the cytoplasm to the nucleus to increase the inflammatory cytokine [ 9 , 10 , 11 ]. Western blot experiments were performed to investigate whether xanthotoxol inhibits the production of inflammatory cytokines through the NF-κB signaling pathway in LPS-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that tobramycin and fosfomycin enhanced melanogenesis via MAPK signaling pathways in B16F10 melanoma cells [ 7 , 8 ]. In addition, it was reported that spiramycin, cycloserine, and nojirimycin attenuate inflammation via NF-κB and MAPK signaling pathways in LPS-induced RAW 264.7 macrophages [ 9 , 10 , 11 ]. Furthermore, we have identified that spiramycin and cycloserine inhibited melanogenesis via MAPK/PKA/AKT signaling pathways in α-MSH-treated mouse melanoma B16F10 cells (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Given the results of DNA expression in the sera, the action mode of both drugs on the parasite may have commenced in the digestive system. Spiramycin is highly concentrated in the bile and macrophages, 45,46 whereas FA helps the hydrolysis of lipids via augmentation of the bile acids secretion 16 . It is suggested that the combined drugs are engaged in the breakdown of lipids required for the membranous structure of parasitophorous vacuole and tachyzoite proliferation in the enterocytes or macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, known as one of the immune cell types, secrete a variety of proinflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and IL-6, as well as inflammatory mediators such as nitric oxide (NO) and prostaglandin E 2 (PGE 2 ), through phosphorylation and activation of the transcription factors nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) [9]. At appropriate levels, pro-inflammatory cytokines and mediators secreted by macrophages act to protect the body from harmful external factors, but in excess, pro-inflammatory cytokines and mediators are known to cause chronic inflammation associated with human inflammatory diseases such as diabetes, inflammatory bowel diseases (IBD), asthma, rheumatoid arthritis, psoriasis, chronic hepatitis, cardiovascular diseases, and various cancers [10].…”
Section: Introductionmentioning
confidence: 99%